Pro Python - Alchin, Marty. (Apress, 2010)
Youve learned the basics of Python, but how do you take your skills to the next stage? Even if you know enough to be productive, there are a number of features that can take you to the next level in Python. Pro Python explores concepts and features normally left to experimentation, allowing you to be even more productive and creative. In addition to pure code concerns, Pro Python will develop your programming techniques and approaches, which will help make you a better Python programmer. Not only will this book help your code, it will also help you understand and interact with the many established Python communities, or even start your own. Take your Python knowledge and coding skills to the next level. Write clean, innovative code that will be respected among your peers. Make your code do more with introspection and metaprogramming. Design complete frameworks and libraries (two are included in the book!). For more information, including a link to the source code referenced in the book, please visit http://propython.com/.